2015
DOI: 10.1109/tie.2014.2361601
|View full text |Cite
|
Sign up to set email alerts
|

Square-Shape Current-Mode Supply for Parametric Control of the DBD Excilamp Power

Abstract: With the aim of providing a power supply for the study of dielectric barrier discharge (DBD) excimer lamps (excilamps), a current-mode converter that allows for an accurate adjustment of the electrical power injected into one of those lamps is designed and implemented. Starting from the electrical model of the DBD lamps, the convenience of using a current-mode supply to control the lamp power is demonstrated. With the proposed converter, the current supplied to the lamp has a trapezoidal almost-square shape co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…As proposed in [19], this current 0093-3813 © 2016 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Methods and Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As proposed in [19], this current 0093-3813 © 2016 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Methods and Equipmentmentioning
confidence: 99%
“…A detailed study concerning the design and operation of this DBD power supply topology can be found in [19] and [20].…”
Section: Methods and Equipmentmentioning
confidence: 99%
“…All the bulbs are filled with the same Xe-Cl mixture, with the same pressure. According to the classical model [5], based on the electrical equivalent circuit (Figure 1-c), the electrical properties of each bulb can be derived: the parameters of this model are: Cg and Cd, the capacitances of the gas gap and of the quartz walls (series connected), and Vth, the threshold voltage, i.e. the minimum value of the gas voltage required to turn on the plasma.…”
Section: Bulb Characteristics and Parametersmentioning
confidence: 99%
“…The power supply which has been selected to carry out the experiments is a square shape current source (the topology is presented on Figure 2[5], together with the main equations), already detailed in [5]: it presents a cascaded structure, associating a DC current source with a current inverter, aimed at controlling the shape of the square current pulses. Its main advantage is the availability of 3 independent degrees of freedom (DOF) to control the ilamp current pulses injected into the bulb: their magnitude I, their frequency f, and their duty cycle D, or their duration D/2f, as shown on 4.…”
Section: Topology Principle and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation